The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/cvi.00390-16
|View full text |Cite
|
Sign up to set email alerts
|

Small-Volume Adenosine, Lidocaine, and Mg 2+ 4-Hour Infusion Leads to 88% Survival after 6 Days of Experimental Sepsis in the Rat without Antibiotics

Abstract: Innovative host-directed drug therapies are urgently required to treat sepsis. We tested the effect of a small-volume 0.9% NaCl adenosine, lidocaine, and Mg 2؉ (ALM) bolus and a 4-h intravenous infusion on survivability in the rat model of polymicrobial sepsis over 6 days. ALM treatment led to a significant increase in survivability (88%) compared to that of controls (25%). Four controls died on day 2 to 3, and two died on day 5. Early death was associated with elevated plasma and lung inflammatory markers (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…In partial support of ALM inhibition of inflammasome signaling, we showed that IL-1β and IL-1α were undetected in plasma at Phase 1 compared to saline controls (50 and 205 pg/ml respectively), and only increased to ~5% of control values after Phase 2 ( Table 2 ). ALM's ability to blunt systemic inflammation parallels a separate study we recently published in the rat model of polymicrobial sepsis, where we showed that a 0.9% NaCl ALM saline 'drip' administered for 4 hours (total volume 1.6 ml) led to little or no systemic inflammation and 88% survivability after 6 days with no antibiotics [ 19 ].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In partial support of ALM inhibition of inflammasome signaling, we showed that IL-1β and IL-1α were undetected in plasma at Phase 1 compared to saline controls (50 and 205 pg/ml respectively), and only increased to ~5% of control values after Phase 2 ( Table 2 ). ALM's ability to blunt systemic inflammation parallels a separate study we recently published in the rat model of polymicrobial sepsis, where we showed that a 0.9% NaCl ALM saline 'drip' administered for 4 hours (total volume 1.6 ml) led to little or no systemic inflammation and 88% survivability after 6 days with no antibiotics [ 19 ].…”
Section: Discussionmentioning
confidence: 58%
“…At high (0.25 to 1 mM) concentrations, ALM arrests the heart, and at lower ‘non-arrest’ concentrations (10-fold less), it resuscitates the heart. The 'non-arrest' ALM bolus and infusion 'drip' treatments have been shown to protect rat and pig models against regional myocardial ischemia, lethal arrhythmias, cardiac arrest, hemorrhagic shock, endotoxemia, infection and sepsis [ 15 , 17 19 ]. A, L and M alone do not confer these benefits [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…What follows is a characterization of the ALM survival phenotype and why it may be applicable to reduce inflammation from a viral attack. (3,207). ALM survival was associated with suppression of the systemic inflammatory response.…”
Section: Adenosine Lidocaine and Mg 2+ Immune-modulatory Functionsmentioning
confidence: 93%
“…We will now briefly review our efforts to develop an intravenous (IV) fluid therapy comprising adenosine, lidocaine and Mg 2+ (ALM) that uniquely protects against trauma and infection, and may be useful as an immune-modulatory agent for coronavirus 2 (SARS-CoV-2), and other viral challenges. Our early experiments focused on traumatic injury (139,(201)(202)(203)(204)(205) and subsequently we showed the same therapy protects against sepsis and endotoxemia in different animal models (3,206,207). The individual effects of A, L or M also have been shown to confer some protection, but not to the same extent as ALM combined (12,208).…”
Section: Adenosine Lidocaine and Mg 2+ Immune-modulatory Functionsmentioning
confidence: 95%
“…7 The ALM bolus and/or infusion treatments have been shown in rat and pig models to protect against regional myocardial ischemia, lethal arrhythmias, cardiac arrest, hemorrhagic shock, coagulopathy, inflammation, endotoxemia, infection and sepsis. [7][8][9][10][11][12] Adenosine, lidocaine and Mg 2+ alone do not confer these benefits. 7 In the present study, we hypothesized that the low-volume ALM drip/infusion may improve physiologic status in the first few hours following a single laparotomy.…”
Section: Introductionmentioning
confidence: 99%